PENGARUH SKILL DAN COMPETENCY TERHADAP KINERJA KARYAWAN PADA PKS PT. SEWANGI SAWIT SEJAHTERA PETAPAHAN KAMPAR - Henrizal Henrizal; Pirmansyah Pirmansyah; Yulizar Yulizar; Adi Setiawan; Dian Prayoga (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
This study aims to determine the effect of skill and competence simultaneously and partially on employee performance at PKS PT. SewangiSawit Sejahtera Kampar, Petapahan. The population in the study consisted of all employees working in the field of sorting and grading, processing, maintenaince, laboratory and administrative and finance fields which opened 60 employees. Determination of the sample in this study using the saturated census method so that the number of samples in this study were 60 respondents. Data analysis was performed using multiple linear regression model. Based on the results of simultaneous hypothesis testing, the skill and competence variables have a very significant influence on employee performance. Based on the results of partial hypothesis testing, skill and competence variables also have an influence on employee performance. The close relationship that occurs between the skill and competence variables on employee performance is very strong with a correlation coefficient (R) of 0.868. While the contribution of the independent variable to the variable is 75.4% while the remaining 24.6% is influenced by other variables not examined in this study.